Cellular Mechanisms of Inflammaging and Periodontal Disease - Clark, Daniel; Radaic, Allan; Kapila, Yvonne (Frontiers in Dental Medicine, 2022)
Increased age is associated with an increased prevalence of chronic inflammatory diseases and conditions. The term inflammaging has been used to describe the age-related changes to the immune response that results in a chronic and elevated inflammatory state that contributes, in part, to the increased prevalence of disease in older adults. Periodontal disease is a chronic inflammatory condition that affects the periodontium and increases in prevalence with age. To better understand the mechanisms that drive inflammaging, a broad body of research has focused on the pathological age-related changes to key cellular regulators of the immune response. This review will focus on our current understanding of how certain immune cells (neutrophils, macrophages, T cells) change with age and how such changes contribute to inflammaging and more specifically to periodontal disease.